Financialization, common stochastic trends, and commodity prices - Kupabado, Moses Mananyi; Kähler, Jürgen (Journal of Futures Markets, 2021)
Commodity financialization has been a subject of discussion since the 2008 financial crisis. It is estimated that between 2003 and 2008, index investors positions increased from 13 billion to 317 billion. Surprisingly, most studies, predominantly based on Granger-causality testing, find no relationship between financialization and commodity prices. We examine the effects of shocks to the common stochastic trends in the index positions, the spot and futures prices of Chicago corn and soybeans, WTI crude oil and Henry Hub natural gas. The results show that financialization has contributed to the price movements of these commodities.
CRIS-Team WoS Importer:2021-10-08

Price effects of commodity financialization: Review of the evidence - Kupabado, Moses Mananyi; Kähler, Jürgen (Journal of Economic Surveys, 2024)
Following the 2007/2008 financial crisis, the price effects of commodity financialization have become an important research topic. We review the empirical evidence, focusing on statistical approaches and econometric models, and find that (1) Granger-causality tests are unable to establish a relationship between commodity futures prices and funds of financial investors, implying a lack of evidence that financialization influences commodity futures prices and (2) studies that use correlation and price spread analysis mostly report evidence of a significant price effect of financialization. Thus, the statistical and econometric approaches adopted by the various studies influence the empirical findings. In addition, data identification may have an impact since economic models and statistical techniques can be sensitive to slight differences in the dataset. Our study of the literature shows that the definition of financialization is open-ended and ambiguous. A theoretical literature review on financialization could be the logical next step.
CRIS-Team Scopus Importer:2024-04-12
Keywords: commodities; financialization; futures prices; Granger-causality; index funds